Reconstruction of the Urban Historical Centre: Contemporary Problems, Difficulties, and Perspectives - Goussous, Jawdat; Hmood, Kabila Faris (Problemy Ekorozwoju, 2023)
Adapting historical city buildings into modern facilities is a basic problem in architecture today. In many large cities, historical centers preserve cultural heritage, including spiritual, cultural, economic, and social capital of irreplaceable value. Because of their importance, these centers must consider the unique characteristics of their surroundings, including harmony of size, spatial composition, architectural environment, facades, and the facilities in general. Disharmony in the architectural design of these centers is evident in the non-compliance of new objects, particularly in historical areas of the city. The restoration, reconstruction, and repair of these historical sites require special knowledge. Experts with this special knowledge can implement modern methods, strategic and operational modes of architecture, and public programs to preserve the historical and cultural values of these sites, thus preserving them for the future, which follows the sustainable development concept. The main conclusion of the research is that unique modern buildings, including novel architectural and constructive elements, can coexist with historical ones by using right policies and methods.